2005
DOI: 10.1149/1.1869273
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Concentration Limitation in Dislocation-Free CZ Silicon Crystals

Abstract: The maximum antimony concentration can be incorporated in a 150 mm Si͑100͒ crystal using the Czochralski ͑CZ͒ crystal growth method was investigated. The antimony limitation was found to be about 5.96 ϫ 10 18 atom/cm 3 ͑0.0084 ⍀ cm͒ using a charge size of 45,000 g. It was limited by the occurrence of constitutional supercooling in the center of the crystal. A ripple or instability in the solid/melt interface was observed in the center of the crystal at the onset of constitutional supercooling. Cellular growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…[6,12,15]. Therefore, it will remain dicult to prove in a certain case whether constitutional supercooling is responsible for a structure loss or whether other phenomena were limiting the dislocation-free growth of heavily doped silicon crystals by the Czochralski technique.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…[6,12,15]. Therefore, it will remain dicult to prove in a certain case whether constitutional supercooling is responsible for a structure loss or whether other phenomena were limiting the dislocation-free growth of heavily doped silicon crystals by the Czochralski technique.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Boron represents the best case, since it has the highest segregation coefficient (k o =0.8-0.73) among all common dopants (see table 1) [3]. The worst case is that of antimony, which has the lowest segregation coefficient (k o =0.023) and for which the lowest resistivity achievable without dislocations has been reported to be around 8.4 mΩ·cm [4]. Phosphorus and arsenic are in an intermediate situation, having a segregation coefficient of 0.35 and 0.3, respectively.…”
Section: Constitutional Supercoolingmentioning
confidence: 99%
“…It was statistically observed that the dislocations form more frequently during the growth of heavily n-type doped crystals (>1x10 19 dopants/cm 3 ) than during the growth of heavily p-type or not heavily doped silicon [6][7][8][9][10]. Furthermore, it was found that dislocation formation in such heavily n-type doped Si crystals takes place more often during the growth stage of the top cone [11] and also its shape affects the risk for dislocation generation [12; 13]: The risk grows with increasing taper angle of the top cone.…”
Section: Introductionmentioning
confidence: 99%